Congregations Talking about Homosexuality: Dialogue on a Difficult Issue - Gaede, Beth Ann (Rowman & Littlefield Publishers, 1999)
Gaede skillfully weaves together the stories of many congregations and how they faced and dealt with the issue of homosexuality. A helpful resource for assisting congregations that seek to engage in dialogue about one of the most difficult faith issues today, the book does not take a theological stand, but rather draws on the experiences of others who have struggled with how to address this issue from a position of respect for all views.